2008
DOI: 10.1044/0161-1461(2008/019)
|View full text |Cite
|
Sign up to set email alerts
|

Training and Self-Reported Confidence for Dysphagia Management Among Speech-Language Pathologists in the Schools

Abstract: Findings support continuing education as a correlate to self-reported confidence to treat dysphagia in the school setting among SLPs in Virginia and its contiguous states. Further research is merited to ascertain if these findings reflect national trends. Quantifiable, cost-effective, and evidenced-based dysphagia training, consultancy, and management models are needed if school-based SLPs are to meet the increasing challenges of their diverse caseloads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Timely assessment and management of children with PFDs is important due to the negative impact they can have on children's health, nutrition, and psychosocial function (Arvedson, 2008;Estrem et al, 2018;Goday et al, 2019;Tutor & Gosa, 2012). However, children's access to pediatric feeding services can be affected by a variety of factors, including distance and travel required (Dew et al, 2013;Fairweather et al, 2016;Raatz, Ward, Marshall, Afoakwah, & Byrnes, 2020;Wilson et al, 2002), the treating speech-language pathologist's (SLP) skill and confidence (Burgess et al, 2016;O'Donoghue & Dean-Claytor, 2008), other family commitments (e.g., work; Breen et al, 2018;Fairweather et al, 2016;Raatz, Ward, Marshall, Afoakwah, & Byrnes, 2020;Wilson et al, 2002), and challenges traveling with children with significant physical needs and/or specialist medical equipment (Nicholl, 2015).…”
mentioning
confidence: 99%
“…Timely assessment and management of children with PFDs is important due to the negative impact they can have on children's health, nutrition, and psychosocial function (Arvedson, 2008;Estrem et al, 2018;Goday et al, 2019;Tutor & Gosa, 2012). However, children's access to pediatric feeding services can be affected by a variety of factors, including distance and travel required (Dew et al, 2013;Fairweather et al, 2016;Raatz, Ward, Marshall, Afoakwah, & Byrnes, 2020;Wilson et al, 2002), the treating speech-language pathologist's (SLP) skill and confidence (Burgess et al, 2016;O'Donoghue & Dean-Claytor, 2008), other family commitments (e.g., work; Breen et al, 2018;Fairweather et al, 2016;Raatz, Ward, Marshall, Afoakwah, & Byrnes, 2020;Wilson et al, 2002), and challenges traveling with children with significant physical needs and/or specialist medical equipment (Nicholl, 2015).…”
mentioning
confidence: 99%
“…The questionnaire used in the current study was developed through modifications and adaptations of available published surveys and guidelines in the area of speech-language pathology (Bateman, Leslie, & Drinnan, 2007;Martino, Pron, & Diamant, 2004;MathersSchmidt & Kurlinski, 2003;O'Donoghue & Dean-Claytor, 2008;Pettigrew & O'Toole, 2007;Speech Pathology Australia, 2004;Ward, Jones, Solley, & Cornwell, 2007). Prior to distribution, clarity and content of the questionnaire was validated by a group of Malaysian and Australian SLPs.…”
Section: Questionnairementioning
confidence: 99%
“…While interdisciplinary teams are presented in the literature as the gold standard for feeding and swallowing intervention, it appears that few schools have assembled such a team. In a large-scale Virginia-area study conducted in 2008, only 7.2% (n=16/222) of speech language pathologists surveyed indicated that their school had a dysphagia team (O'Donoghue & Dean-Claytor, 2008). A Vermont-based study of 52 ASHA-certified SLPs also reported a lack of support and infrastructure for feeding and swallowing management in the school system.…”
Section: Current Dysphagia Management Practices In the School Settingmentioning
confidence: 99%